Opinions of Polish Roman Catholic Clergy on Archaeological Research Conducted on Church Premises: A Pilot Study - Drewicz, Mateusz; Pawleta, Michał (Analecta Archaeologica Ressoviensia, 2026)
The aim of the article is to present and discuss the opinions of Polish Roman Catholic clergy on archaeological research carried out in areas under the church’s management. The article provides the research context of the said archaeological research within the framework of public archaeology. The study used the method of individual in-depth interviews (IDIs) conducted between February 20 and May 29, 2024 in selected Roman Catholic parishes and rectories in Poland. The interviews (IDIs) were conducted with parish priests and rectors of parishes and churches where archaeological research had previously taken place. Six categories were considered in the study: opinions of the clergy, opinions of the congregation as perceived by the clergy, reasons for conducting archaeological research, preservation of monuments, recommendations of the clergy to archaeologists, and future cooperation with archaeologists. The research was interdisciplinary, involving scientists from the humanities and social sciences. The results of the study led to the emergence of different research perspectives.